The challenges of collaborative working: Bridging the gap between research and practice - Thompson, S. W.; Rogerson, D.; Bell, L.; Hembrough, D. (International Universities Strength and Conditioning Association Journal, 2020)
'Evidence-based practice', 'applied sport science' and 'bridging the gap': notions that frequent academic publications, underpin practice models and theme conference presentations. Conceptually similar, these terms both highlight and redress the estrangement between research and practice. No more apparent is this than within the field of Strength and Conditioning (S&C), where practices and methods are often developed by practitioners within clubs and organisations out of necessity that are later investigated and published within academia. Evidence-based practice was introduced within medicine in the early 90's, where research (high impact, peer-reviewed publications), clinical expertise (experience and knowledge of the patient) and the patient preferences (including the patient in the decision for courses of action) were triangulated as a means of working more systematically and holistically 123. Attempts to translate this model into S&C have been happening for some time (figure 1) with limited success, however. Despite their apparent simplicity in design and development, such approaches have proven to be difficult to implement in practice.